The effect of different feeding system on fatty acids composition of cow's milk - Juráček, Miroslav (Acta fytotechnica et zootechnica, 2020)
The aim of the experiment was study the effect of different feeding system on fatty acids (FA) profile of cow’s milk. The tank’s samples from two farms were collected. On these farms breed: the Slovak Spotted cattle was reared. Feeding system was realized on the base pasture + supplementary feeding without silage – grazing feeding system (farm A) and silage feeding system (farm B). The FA profile in the milk samples with the apparatus (Agilent 6890A GC, Agilent technologies, USA) were analysed. Feeding system affects FA profile of cow’s milk. Significantly higher proportion of FA in milk samples: C4:0, C17:0, C18:1 cis-n9, C18:2 cis-n9, C18:3-n3 and C20:0 in milk from grazing feeding system (farm A) was detected. The samples of milk only from this feeding system contained C20:5 n3. Significantly higher content of 18:2 cis n6 and presence of C13:0, C20:3 n6 and C20:4 n6 only in milk samples from silage feeding system were determined. Significantly lower proportion of saturated FA was typical for milk from farm A and significantly higher proportion of polyunsaturated FA was characteristic for the samples from farm B. The influence of the feeding system on the monounsaturated FA content was not confirmed. In milk samples from both feeding systems very different n6/n3 FA ratio was detected, with lower value for milk from grazing feeding system (1.36 vs. 9.12).